Pelatihan Implementasi Sistem Pembelajaran Digital Berbasis Kecerdasan Buatan (AI) untuk Meningkatkan Kemandirian Belajar Siswa dan Kompetensi Guru di SMA RK Deli Murni Deli Tua - Rafika Sari Br Sembiring; Oktaviana Bangun; Berlin Barus; Darwin Siallagan (Jurnal Pengabdian Pada Masyarakat METHABDI, 2026)
This community service program addresses the low digital literacy of teachers and the suboptimal use of technology in learning at SMA RK Deli Murni Deli Tua. The program aims to enhance teacher competence in utilizing artificial intelligence (AI)-based learning platforms and foster student learning independence. The implementation method employed participatory training and mentoring, including material presentations on AI concepts in education, hands-on practice using AI platforms for instructional media development, and independent implementation assistance. The program involved 25 teachers and 40 students. Results showed a significant increase in teacher understanding of AI utilization (from 35% to 88% based on pre-test and post-test assessments) and the successful development of AI-assisted digital learning tools by participating teachers. Students also demonstrated improved learning independence, reflected in increased active participation and ability to access independent learning resources. This program is expected to serve as a model for digital transformation in secondary education.